Construction of green fluorescent protein in an inducible vector - Nurul Nadiah, Binti Jalaludin (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Green Fluorescent Protein (GFP) has been used extensively as a reporter gene in many transformations of organisms. This reporter gene can be used in organism by inserting the gene in a vector construct. In this study, an inducible vector was done by reconstructing the binary vector pGPTV-SRN4/AGS to include the GFP gene. The construction of plasmid was started with the preparation of intermediary construct; 1.8 kb of GUS region of pAGS was removed using the restriction enzyme, Sma!. This GUS region was replaced by the insertion of 750 bp SmaIlHindII fragment of pMCB30 which contains sGFPS65T that encodes for the GFP gene. Then, the binary vector pGPTV-SRN4/AGS-GFP was made by the insertion of HindIII fragment from pAGS-GFP into HindIII site of the vector. The introduction of this vector that contain reporter gene GFP into competent cell E. coli was done through heat-shock and electroporation method. Analysis of transformants was done through Polymerase Chain Reaction (PCR). The intennediary construct containing GFP gene was successfully done.